Law Part of the Framework for Accountability in Policy Interpretation and Practice - Abbasi, Vanessa; Marzieh, Karolina (SCAD Independent, 2017)
Law can increasingly be seen as part of the framework for accountability in policy interpretation and practice. This is reflected in important judgments in the UK and European context, where courts have been proactive in challenging restrictive interpretations by agencies of their legal duties, or even by parliament in law-making that is incompatible with the European Convention on Human Rights and Fundamental Freedoms. Without attention to the practice environment for legal and ethical practice, the role of law in welfare reform will be compromised, however robust the legal framework. Subsequently, empirical work has explored how social workers learn about the law, in both practice and academic environments, and how they use that learning. This paper considers the complex relationships between law, welfare policy and social work practice, to address the question of what role legal frameworks might play in achieving welfare policy and professional practice goals. These debates illustrate is the essentially contested nature of the relationship between law and practice and the delicate balance between law and ethics within a framework for professional accountability. It is hardly surprising, perhaps, that law is often seen by practitioners as alien and hostile territory.